If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(y + -8) = 9y + -56 Reorder the terms: 7(-8 + y) = 9y + -56 (-8 * 7 + y * 7) = 9y + -56 (-56 + 7y) = 9y + -56 Reorder the terms: -56 + 7y = -56 + 9y Add '56' to each side of the equation. -56 + 56 + 7y = -56 + 56 + 9y Combine like terms: -56 + 56 = 0 0 + 7y = -56 + 56 + 9y 7y = -56 + 56 + 9y Combine like terms: -56 + 56 = 0 7y = 0 + 9y 7y = 9y Solving 7y = 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. 7y + -9y = 9y + -9y Combine like terms: 7y + -9y = -2y -2y = 9y + -9y Combine like terms: 9y + -9y = 0 -2y = 0 Divide each side by '-2'. y = 0 Simplifying y = 0
| 10+5(2-2x)=0 | | h=245+16x^2 | | 245=-16t^2+h | | y=(2y)+15 | | 7x+21x-8=7(4x+9) | | (y^2+4y+4)(y+2)= | | 2x^3=129 | | 8m-7=5m+11 | | z(t)=120(1/2)^t/32760 | | -16t^2-h+245=0 | | 6=1-3z | | 4x+x^2-25=2304 | | 19x-3=21X-5 | | 5x+19x-7=6(4x+3) | | 14x-118=62+5x | | h=-16t^2-11t+120 | | 2x-187=72-5x | | 2x-(x-1)=5(x-3) | | 42x^2-5x-3=0 | | -20=2(w+7)-4w | | t/25=14/10 | | -9x-73=67-14x | | 4x+26x-9=6(5x+5) | | 3x-6=40 | | 3x-6+2x-4=30 | | 5x-40=8x+11 | | 28-4x=13-9x | | -161+8x=2x+99 | | 12x+15=5x+7 | | (x-1)+(x-1)=g | | y-2=(22-y)^(1/2) | | -114-2x=210+7x |